Priming grapevines with oregano essential oil vapour results in a metabolomic shift eliciting resistance against downy mildew - Ana Cecilia Aliaga Fandino; Nicolas Vigneron; Esteban Alfonso; Jean-Philippe Burdet; Eric Remolif; Amanda Malvessi Cattani; Tara Smit-Sadki; Stéphanie Cluzet; Josep Valls-Fonayet; Pierre Pétriacq; Markus Rienth (BMC Plant Biology)
Abstract Background Priming plants with natural products is extensively studied in the agricultural field to reduce the use of synthetic and copper-based pesticides. Previous studies have shown that Oregano essential oil vapour (OEOV) is an effective priming agent against downy mildew (DM) in grapevine (Vitis vinifera L. cv. Chasselas), activating different transcriptomic regulated defence mechanisms. Results In the present study, we complement transcriptomic data with metabolomic insights, confirming some previous regulating patterns and highlighting new mechanisms underlying OEOV-induced resistance. A significant modulation of the phenylpropanoid pathway was noted. The data also confirmed the induction of an oxidative stress response indicated by an up-regulation of reactive oxygen species (ROS)-related genes and a congruent depletion of putative L-glutathione. Interestingly, OEOV promoted the accumulation of organic metabolites such as terpenes and other potential phytoalexins, which could potentially contribute to grapevine innate immune response to Plasmopara viticola. Conclusion Overall, this study uncovered a diverse influence of OEOV on V. vinifera defence mechanisms against DM, enhancing our comprehension of the mode of action of essential oils. This insight offers various prospects for crafting innovative biocontrol products, fostering a more dynamic and sustainable approach to agriculture.